2010
DOI: 10.17221/46/2009-rae
|View full text |Cite
|
Sign up to set email alerts
|

Study of knotweed (Reynoutria) as possible phytomass resource for energy and industrial utilization

Abstract: Strašil Z., Kára J., 2010. Study of knotweed (Reynoutria) as possible phytomass resource for energy and industrial utilization. Res. Agr. Eng., This paper deals with the Reynoutria × bohemica and Reynoutria japonica under conditions of the Czech Republic. It evaluates the impact of soil, weather conditions and various terms of harvest (autumn, spring) on the yield, dry matter content, phytomass loss, ash content, and basic elements content change in plants. Heavy metals content was determined in soil where pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 4 publications
2
12
0
4
Order By: Relevance
“…Another research of related to the energy potential of Japanese knotweed indicated its high energy potential and satisfactory chemical composition for direct combustion purposes. In accordance to the mentioned information it can be concluded that there is a possibility of subsequent utilization of Japanese knotweed waste biomass as a feedstock for briquette fuel production due to the current plant extension, effort to exterminate already the existing plant population and the plant high biomass yield and energy potential [12].…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…Another research of related to the energy potential of Japanese knotweed indicated its high energy potential and satisfactory chemical composition for direct combustion purposes. In accordance to the mentioned information it can be concluded that there is a possibility of subsequent utilization of Japanese knotweed waste biomass as a feedstock for briquette fuel production due to the current plant extension, effort to exterminate already the existing plant population and the plant high biomass yield and energy potential [12].…”
Section: Introductionsupporting
confidence: 56%
“…Energy potential of Japanese knotweed proved its suitability for combustion properties, thus, for energy production in the form of briquette biofuel. The gross calorific value of Japanese knotweed was determined in the previous study equal to 18.4 MJ·kg -1 [12]. The energy potential of the investigated feedstock material exceeded the energy potential of other waste biomass, namely, the gross calorific value of forest wood residues was proved equal to 18.7 MJ·kg -1 and equal to 17.2 MJ·kg -1 for oat grain residues [21].…”
Section: Chemical Analysismentioning
confidence: 99%
“…Of the four studied herbaceous invasive alien species (IAS), the highest annual biomass yield was observed for F. japonica and S. gigantea , 8.61 and 8.64 ton DM per hectare respectively. Strašil and Kára measured a comparable biomass production in the Czech Republic for F. japonica with the same harvest regime (9.06 ton DM ha −1 ). Impatiens glandulifera and H. mantegazzianum had a lower biomass yield (5.78 and 6.04 ton DM ha −1 ) but still produced more biomass than the most productive herbaceous Low‐Input High‐Diversity (LIHD) systems in conservation areas in the same study area (Fig ) .…”
Section: Discussionmentioning
confidence: 83%
“…Second generation bioenergy crops avoid competition with food and feed production, reduce the environmental impacts of fertilizers and herbicides, and enhance biodiversity in the landscape (Gomez et al, 2008;Havlík et al, 2011;Naik et al, 2009). Especially herbaceous perennials have great potentials to fulfill these criteria and various new species for bioenergy production have been tested, e.g., Miscanthus giganteus, Silphium perfoliatum, Sida hermaphrodita and Fallopia x bohemica (Borkowska and Molas, 2012;Franzing et al, 2014;Lewandowski et al, 2000;Pude andFranken, 2001, Lewandowski andHeinz, 2003;Strašil and Kára, 2010). The Giant Knotweed, or Sakhalin Knotweed (Fallopia sachalinensis), grows natively on the Russian island of Sakhalin, in Japan and on the Korean peninsula.…”
Section: Introductionmentioning
confidence: 99%